The family the secret fundamentalism at the heart of American power - Sharlet, Jeff (New York, NY [u.a.] HarperCollins, 2008)
Awakenings. Ivanwald ; Experimental religion ; Revival machine -- Jesus plus nothing. Unit number one ; The F word ; The ministry of proper enlightenment ; The blob ; Vietnamization ; Jesus + 0 = X ; Interesting blood -- The popular front. What everybody wants ; The romance of American fundamentalism ; Unschooling ; This is not the end
Draws on the author's experiences living undercover within the ranks of "the Family" theocratic group in Arlington, Virginia, to explore fundamentalism in America and its role in influencing democracy
Includes bibliographical references (p. [393]-432) and index
Archivierung prüfen
Archivierung prüfen
Keywords: Fellowship Foundation (Washington, D.C.); Fundamentalism -- Political aspects -- United States; Christianity and politics -- United States; Religious Right -- United States; Christian conservatism -- United States; Church and state -- United States; Neue Christliche Rechte; Politik; Christentum; Konservativismus; Christian fundamentalism; Christianity and politics; Christianity and politics -- United States; Religious Right -- United States; Church and state -- United States; Usa